The last hope - Hunter, Erin. (New York, NY : Harper, an imprint of HarperCollins Publishers, 2015)
Jayfeather, Dovewing, and Lionblaze continue to unravel the mysterious prophecy that has brought them together, but, as their battle against the Dark Forest approaches, the trio will need help from Firestar, ThunderClan, and StarClan if they want to save the clans.
"Warriors adventure game inside"--Back cover.
4.0
5-8
5-8
560L
560L
Keywords: Cats -- Juvenile fiction; Prophecies -- Juvenile fiction; Cats -- Fiction; Prophecies -- Fiction; Cats -- Fiction; Prophecies -- Fiction